2020
DOI: 10.1186/s40510-020-00342-4
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the magnitude, parallelism, and asymmetry of micro-implant-assisted rapid maxillary expansion in non-growing patients

Abstract: Background and objectives Micro-implant-assisted expanders have shown significant effects on the mid-face, including a degree of asymmetry. The aim of this study is to quantify the magnitude, parallelism, and asymmetry of this type of expansion in non-growing patients. Methods A retrospective study on a sample of 31 non-growing patients with an average age of 20.4 years old, with cone beam computed tomography images taken before and right after exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 18 publications
2
26
2
4
Order By: Relevance
“…21,22 MSE is a well-documented type of MARPE that exploits the concept of producing a posterior force vector by the posterior positioning of jackscrew and a more stable anchorage by the bicortical engagement of its four mini-screws, which produces a parallel pattern of skeletal expansion in the horizontal plane. [23][24][25][26][27] Traditionally, MSE appliances are manufactured on stone models. In a recent publication, digital planning of MSE based on a patient's CBCT image has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 MSE is a well-documented type of MARPE that exploits the concept of producing a posterior force vector by the posterior positioning of jackscrew and a more stable anchorage by the bicortical engagement of its four mini-screws, which produces a parallel pattern of skeletal expansion in the horizontal plane. [23][24][25][26][27] Traditionally, MSE appliances are manufactured on stone models. In a recent publication, digital planning of MSE based on a patient's CBCT image has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in order to avoid the potential risk of damaging anatomical structures, Cantarella et al [36] suggested that the deployment of 3D virtual surgical planning using digital data might be advantageous prior to undertaking MSE. Elkenawy et al [37] were also interested in the biomechanics of MSE. In their study, they noted that over half of approx.…”
Section: Surgical Midfacial Expansionmentioning
confidence: 99%
“…Micro-implant-assisted expanders have proved significant effects on the mid-face, with a degree of asymmetry [49]. On non-growing patients, CBCT images showed a statistically significant difference between the average magnitude of the total expansion of 4.98 mm at the anterior nasal spine and the average of 4.77 mm at the posterior nasal spine.…”
Section: Use In Orthodontic Clinical Practice and Dento-facial Orthopedicsmentioning
confidence: 99%